Uji daya gabung tiga galur mandul jantan dengan sepuluh galur kandidat restorer pada tanaman padi (Oryza sativa L.) - Aisah, Siti; Hayati, Erita; Bakhtiar, Bakhtiar (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala)
The purpose of this research was to obtain lines of candidates restorer that has a good combining ability against three plants Cytoplasmic Male Sterile (CMS/A). The research was conducted at the research field at PT. Syngenta Indonesia Cikampek West Java, Jati Sari, Balonggandu village. Crossed design andÂ analysis arranged by followingÂ line x tester desing. Ten hybrid line restorer fertility and three line CMS planted the field using randomized complete block design withÂ 2 replications, treatment consisting of 43 treatment so getting 86 unit experiment with the analysis resources combining ability. This research was the observed against character of high of plants, number of filled grain per clump , number of filled per clump, number of unfilled per clump, weights 1000 grains, number of productive, panicle length, persentase fertiliy panicle. The result showed that all the characters observed having had significant variance of general combining ability (GCA) and specific combining ability (SCA). Expression of the characters above controlled by the action of genes additive or non-aditif.